HUBUNGAN MANAJEMEN KELAS DAN KEPRIBADIAN DOSEN DENGAN DISIPLIN KULIAH MAHASISWA DI FAKULTAS TARBIYAH DAN ILMU KEGURUAN (FTIK) IAIN PADANGSIDIMPUAN - LIS YULIANTI SYAFRIDA SIREGAR (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2016)
The aim of this research was to know the correlation between class management and lecturer’s characteristic to the students’ learning discipline. This research has been done by  correlation type. The instrument used in this research is questionnaires of class management, characteristics of the lecturer, and students’ disciplines. Data have been analyzed by statistical way by using SPSS. The result of this research was there was significant correlation between class management with students’ learning discipline (correlation between X1 dan Y), had correlation of coefficient was 0.47, it meant that class management can influence students’ learning discipline. Then, there was significant correlation between lecturer’s characteristic with students’ learning discipline (correlation between X2 and Y) had correlation of coefficient was 0.733. The correlation of coefficient was 0.61, it meant if class management and lecturer’s characteristic in unity, so it could influence students’ learning discipline. While, the significant between three variables was F count F table(13,05 3,22). So, there was significant correlation between variable  X1 and variable X2 to variable Y. It could be seen F count was bigger than F table. The hyphothesis is accepted.